2007
DOI: 10.1097/qai.0b013e3180690d6a
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic and Evolutionary Trends of HIV-1 CRF31_BC-Related Strains in Southern Brazil

Abstract: CRF31_BC plays an important role in the HIV epidemic of southern Brazil, and its prevalence has increased throughout the years. This circulating recombinant form corresponds to approximately 25% of total HIV isolates in this region in 2004. Understanding the cause of this spread is important for public health strategies in Brazil and in Latin America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
42
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 27 publications
8
42
0
3
Order By: Relevance
“…3,4,7,14,[19][20][21] No presente trabalho, a elevada prevalência do subtipo C e da CRF31_BC foi observada também no município de Canoas, com freqüências ainda mais elevadas (de 43,8% e 35,0%, respectivamente) do que em outros locais do estado. Foram ainda encontrados os subtipos B e F (18,8% e 2,4%, respectivamente), não tendo sido observados outros subtipos.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…3,4,7,14,[19][20][21] No presente trabalho, a elevada prevalência do subtipo C e da CRF31_BC foi observada também no município de Canoas, com freqüências ainda mais elevadas (de 43,8% e 35,0%, respectivamente) do que em outros locais do estado. Foram ainda encontrados os subtipos B e F (18,8% e 2,4%, respectivamente), não tendo sido observados outros subtipos.…”
Section: Discussionunclassified
“…23 Essa situação provavelmente também ocorre com a CRF31_BC, na medida em que a maior parte do genoma é do subtipo C, com uma pequena inserção do B na região do gene da transcriptase reversa. 14,19 A esse aspecto soma-se um forte efeito fundador, pois o subtipo C e o recombinante CRF31_BC estão circulando há mais de 20 anos no RS, tendo sido introduzidos em etapas iniciais da epidemia da Aids no estado. 2,15,19 Ainda não se sabe se essas variantes também tiveram alguma vantagem evolutiva por pressão antrópica, principalmente devido ao uso intensivo dos medicamentos anti-retrovirais, que podem ter alterado a composição da população dos vírus como quasiespécies e favorecido a emergência de cepas resistentes, gerando novos diferenciais de transmissibilidade e capacidade reprodutiva (fi tness).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Several studies have reported an increase in HIV-1C prevalence in that region. [8][9][10][11][12][13][14][15][16] In the city of Rio Grande, one of the foci of this study, such an increase is clearly evident: from 22% in 2002 to 56% in 2010. 16,17 The introduction of highly active antiretroviral therapy (HAART) in HIV-infected patients is associated with a marked reduction in morbidity and mortality.…”
Section: Introductionmentioning
confidence: 87%
“…Currently, depending on the state, 27-79% of HIV infections are caused by HIV-1C, 23-45% by HIV-1B, 3-29% by CRF31 BC and other BC recombinants, and HIV-1F and its recombinants account for up to 10% of infections. [6][7][8][9][10][11][12][13][14][15][16] Recent studies suggest that the HIV-1 epidemics in Brazil has initiated with multiple introductions of HIV-1B during the 60s or 70s 17,18 in the largest cities of Southeast, and then disseminated throughout the country. HIV-1F and C had a monophyletic entry in the country, the former in the Southeast and the latter in the South, approximately 10-15 years after HIV-1B.…”
Section: Introductionmentioning
confidence: 99%